Method for Document Management Process Mining - Terminas, Rolandas; Ramanauskaitė, Simona (Jaunųjų mokslininkų darbai, 2020)
The paper briefly overviews the importance of process mining and its applications and scientific works on process mining used for the analysis of financial activities or audit. Drawing on the overviewed works, a method for document management processes mining has been presented. This method is based on the analysis of log records of the document management system. The method provides process graphs, but there is not enough data to clearly identify what is happening at each node or vertex. This requires human assistance in naming each activity. Additionally, recommendations to address this flaw by integrating more system data have been provided.
Keywords: process mining; document management system; log records; process graph